FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT DEPRESI PADA PASIEN KANKER PAYUDARA YANG SUDAH MENDAPATKAN TERAPI DI RUMAH SAKIT MARGONO SOEKARJO PURWOKERTO - Wijayana, Kamal Agung; ., Suharmilah; Budi Setyaningsih, Tri Rini (Jurusan Kedokteran FK Unsoed, 2013)
Prevalence of depression in Indonesia is currently quite high. Depression is caused by internal and external factors. External factors that can cause depression for example, medical disease . One of the medical illnesses associated with the incidence of depression is breast cancer. Depression in breast cancer can occur because of the sense of loss such as loss of body shape. The purpose of the research was to discover the factors associated with level of depression in breast cancer patients who had therapy at Margono Soekarjo Hospital Purwokerto. The subjects of the research was breast cancer outpatient who had therapy at Margono Soekarjo Hospital Purwokerto in 2011. The dependent variable in this research was level of depression which measured by the BDI questionnaire (Beck Depression Inventory). The independent variables in this research was term of diagnosis, disease stage and therapy in breast cancer patients who had therapy. The Method of this research was an observational analytic with cross sectional design. The sampling technique used consecutive sampling with 66 samples. Univariate analysis was used to see the frequency distribution of variables and Spearman test and the Contingency Coefficient test for bivariate analysis. The result of the statistical analysis revealed that there was no relationship between the term of diagnosis p = 0,289 (p> 0,05) and stage of disease p = 0,354 (p> 0,05) with level of depression, but there was a relationship between therapy with level of depession p = 0,001 (p< 0,05). The conclusion of the research was there was significant correlation between negative direction and therapy with level of depression in breast cancer patients who had therapy at Margono Soekarjo Hospital Purwokerto.